DYNAMIC PROCESSES OCCURRING AT THE CRIIIAQ-MANGANITE (γ-MNOOH) INTERFACE: SIMULTANEOUS ADSORPTION, MICROPRECIPITATION, OXIDATION/REDUCTION, AND DISSOLUTION - Weaver R.M.; Hochella M.F.; Ilton E.S. (My University, 2002)
The complex interaction between CrIIIaq and manganite (γ-MnOOH) was systematically studied at room temperature over a pH range of 3 to 6, and within a concentration range of 10-4 to 10-2 M CrOH2+aq. Solution compositional changes during batch reactions were characterized by inductively coupled plasma spectroscopy and ultraviolet-visible spectrophotometry. The manganites were characterized before and after reaction with X-ray photoelectron spectroscopy, scanning electron microscopy (SEM), high-resolution field-emission SEM, and energy-dispersive spectroscopy analysis. Fluid-cell atomic force microscopy was used to follow these metal-mineral interactions in situ. The reactions are characterized by (1) sorption of CrIII and the surface-catalyzed microprecipitation of CrIII-hydroxy hydrate on manganite surfaces, (2) the acidic dissolution of the manganite, and (3) the simultaneous reductive dissolution of manganite coupled with the oxidation of CrIIIaq to highly toxic CrVIaq. CrIII-hydroxy hydrate was shown to precipitate on the manganite surface while still undersaturated in bulk solution. The rate of manganite dissolution increased with decreasing pH due both to acid-promoted and Mn-reduction-promoted dissolution. Cr oxidation also increased in the lower pH range, this as a result of its direct redox coupling with Mn reduction. Neither MnII nor CrVI were ever detected on manganite surfaces, even at the maximum rate of their generation. At the highest pHs of this study, CrIIIaq was effectively removed from solution to form CrIII-hydroxy hydrate on manganite surfaces and in the bulk solution, and manganite dissolution and CrVIaq generation were minimized. All interface reactions described above were heterogeneous across the manganite surfaces. This heterogeneity is a direct result of the heterogeneous semiconducting nature of natural manganite crystals and is also an expression of the proximity effect, whereby redox processes on semiconducting surfaces are not limited to next nearest neighbor sites.